2016
DOI: 10.1093/nar/gkw308
|View full text |Cite
|
Sign up to set email alerts
|

LassoProt: server to analyze biopolymers with lassos

Abstract: The LassoProt server, http://lassoprot.cent.uw.edu.pl/, enables analysis of biopolymers with entangled configurations called lassos. The server offers various ways of visualizing lasso configurations, as well as their time trajectories, with all the results and plots downloadable. Broad spectrum of applications makes LassoProt a useful tool for biologists, biophysicists, chemists, polymer physicists and mathematicians. The server and our methods have been validated on the whole PDB, and the results constitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…Finally we note, that based on the tools described in this paper, a systematic review of the whole PDB has already been conducted and all identified proteins with lasso motifs (including those presented in this paper) are deposited in the LassoProt database44. We are convinced that analysis of all those structures and their lasso motifs deserves further thorough studies.…”
Section: Discussionmentioning
confidence: 82%
“…Finally we note, that based on the tools described in this paper, a systematic review of the whole PDB has already been conducted and all identified proteins with lasso motifs (including those presented in this paper) are deposited in the LassoProt database44. We are convinced that analysis of all those structures and their lasso motifs deserves further thorough studies.…”
Section: Discussionmentioning
confidence: 82%
“…To identify stable links in proteins, we analyzed their structure and used the method of spanning the (triangulated) minimal surface (17,18). A segment of a protein chain forms a covalent loop if the ends of the segment are connected by a covalent bond (e.g., disulfide bridges).…”
Section: Search For Linksmentioning
confidence: 99%
“…2). The indexes of the cysteines are known from the protein structure, whereas indexes of loop-piercing residues can be determined from minimal surface analysis used in the classification of lasso proteins (17,18). This method is general and can be applied to various intramolecular contacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7, 8 In addition to these knotted systems in which the entanglements are formed solely by the protein backbone, other knot-like proteins and peptides are established via covalent sidechain-sidechain or sidechain-backbone crosslinks. A protein example of this type of entangled structure is the cytokine leptin 9 which exhibits a “pierced lasso” architecture 10, 11 formed by a disulfide bond. A well-studied example of knotting caused by disulfide bonding is the cystine knot motif, which occurs both in peptides 12 and in larger proteins.…”
Section: Introductionmentioning
confidence: 99%